Molecular Detection of Ureaplasma urealyticum from Prostate Tissues using PCR-RFLP, Tehran, Iran - Gholamreza Irajian; Mehri Sharifi; Shiva Mirkalantari; Reza Mirnejad; Mohammad reza Jalali Nadoushan (Iranian Society of Pathology, 2016)
Background: In most cases, prostatitis can be caused by a bacterial agent such as Ureaplasma urealyticum. Considering to the cumbersome of the culture method for the detection of Ureaplasma species in clinical samples such as prostate; PCR method that is faster and more appropriate than the cultivation methods, can be utilized for the detection of U. urealyticum and U. parvum. PCR-RFLP method can differentiate both biovars and assist in studies of the clinical diagnosis, epidemiology and pathology of this species in human. The aim of this study was to molecular detection of U. urealyticumin in prostate tissue samples based on PCR- RFLP. Methods:Two hundred prostate tissue samples were collected from patient suffering from prostatitis. The PCR assay was used to amplify a 559 bp fragment of 16S-23SRNA interspace region of Ureaplasma. After sequencing, PCR products from positive samples were digested with TaqI restriction enzyme. Results: Seven cases (3.5%) out of 200 prostate tissue samples were positive for U. urealyticum. Results of PCR products sequencing demonstrated that all isolates were U. parvum biovar. PCR-RFLP results shown that there was not any differentiation in pattern of enzymatic digestion, in addition, all isolates were U. parvum, serovar 3. Conclusion: U. urealyticum can be one of the causing agents of prostatitis. Using PCR-RFLP with specific primer and restriction enzyme is a rapid and cost-effect method for detection and differentiation of Ureaplasma from clinical samples.